Antiplasmodial Activity and Toxicological Assessment of Curcumin PLGA-Encapsulated Nanoparticles - Busari, Zulaikha A.; Dauda, Kabiru A.; Morenikeji, Olajumoke A.; Afolayan, Funmilayo; Oyeyemi, Oyetunde T.; Meena, Jairam; Sahu, Debasis; Panda, Amulya K. (Frontiers in Pharmacology, 2017)
Curcumin is a polyphenolic pigment isolated from the rhizomes of Curcuma longa (turmeric), a medicinal plant widely used in the ancient Indian and Chinese medicine. The antiplasmodial activity of curcumin is often hampered by its fast metabolism and poor water solubility, thus its incorporation into a delivery system could circumvent this problem. This study aimed to evaluate the in vivo antiplasmodial activity and the toxicity assessment of curcumin incorporated into poly (lactic-co-glycolic) acid (PLGA) nanoparticles. Curcumin was loaded with poly (D,L-lactic-co-glycolic acid) (PLGA) using solvent evaporation from oil-in-water single emulsion method. The nanoparticles were characterized and evaluated in vivo for anti-malarial activities using Peter’s 4-day suppressive protocol in mice model. Hematological and hepatic toxicity assays were performed on whole blood and plasma respectively. In vivo anti-parasitic test and toxicity assays for free and encapsulated drug were performed at 5 mg/kg and 10 mg/kg. In vitro cytotoxicity of free and PLGA encapsulated curcumin (Cur-PLGA) to RAW 264.7 cell line was also determined at varying concentrations (1000-7.8 µg/mL). The size and entrapment efficiency of the nanoparticulate drug formulated were 291.2±82.1 nm and 21.8±0.4 respectively. The percentage parasite suppression (56.8%) at 5 mg/kg was significantly higher than in free drug (40.5%) of similar concentration (P<0.05) but not at 10 mg/kg (49.5%) at 4-day post-treatment. There were no significant differences in most of the recorded blood parameters in free curcumin and PLGA encapsulated nanoparticulate form (P>0.05) except in lymphocytes which were significantly higher in Cur-PLGA compared to the free drug (P<0.05). There were no significant differences in hepatotoxic biomarkers; aspartate aminotransferase (AST) and alanine aminotransferase (ALT) concentrations in various treatment groups (P>0.05). At higher concentrations (1000 and 500 µg/mL), Cur-PLGA entrapped nanoparticle showed higher toxicity compared with the free drug (P<0.05) in exposed RAW 264.7 cell line. The cell viability was however higher in Cur-PLGA nanoparticles than in free curcumin at lower concentrations (P>0.05). The antiplasmodial activity and safety of Cur-PLGA was better at lower concentration.